Spatial effects of transeuropean networks: Preliminary results from a spatial computable general equilibrium analysis - Johannes Bröcker (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 1998)
This paper quantifies regional welfare effects of new transport links, which are going to be established in the framework of Trans-European Networks (TEN). It is confined to the regional welfare effects resulting from the use of the new links for trading goods and services. Effects from the construction phase, from financing and maintenance are not considered. Use of the links for other than trade purposes, such as commuting, tourism, leisure trips et cetera are not considered either. Welfare implications of new transport links are quantified by simulating effects of transport distance reductions in a spatial computable general equilibrium model. We model a static equilibrium for two sectors (local goods and tradables) and many regions. Firms in the tradables sector supply a large number of symmetrical product varieties under monopolistic competition. Trade between regions is costly, with costs depending on transport distances through a given transport network as well as on national trade impediments. The paper explains the formal structure of the model, the calibration procedure, and the data basis for implementing the model to a system of more than 800 regions covering the entire European space. Numerical results for several scenarios regarding regarding the establishment of TEN links are presented.
Keywords: 330; transport infrastructure; computable equilibrium; spatial equilibrium; monopolistic competition